Psychological and Demographic Predictors of Vaping and Vaping Susceptibility in Young Adults - Teah, Grace E.; Conner, Tamlin S. (Frontiers in Psychology, 2021)
Background: The use of electronic nicotine delivery systems (ENDS), is becoming popular among young adults. Few studies have explored the psychological factors that predict ENDS use and susceptibility in young adults, in addition to known demographic predictors. Method: In a cross-sectional survey design, 521 young adults (37% male), ages 18-25 from the United States, were recruited via MTurk in 2019, to answer an online survey measuring demographic, and psychological measures related to mental health, and the Big Five personality traits. The survey also included measures of ENDS ever-use, current use, and susceptibility (never users open to trying ENDS), which we predicted from the demographic and psychological measures using binary logistic regression analyses. Results: Of those surveyed (n=521), 282 (54.1%) were ENDS ever-users, 93 (17.9%) were current ENDS users, and 61 (11.7%) were ENDS susceptible. Demographically, young adults lower in adulthood SES, not pursuing education further than high school, and current smokers were more likely to be ENDS users. Psychologically, young adults with mental health issues, higher in neuroticism, and lower in conscientiousness were more likely to have ever-used ENDS; only higher perceived stress and lower conscientiousness was associated with current ENDS use. Only conscientiousness predicted ENDS susceptibility. Conclusion: Young adults with experience in vaping, were more demographically and psychologically vulnerable than young adults with no experience in vaping. Young adults interested in vaping without prior experience, were less conscientious than their non-interested peers. Interventions to target vaping use should focus on economically and psychologically disadvantaged young adults.